The stigma of disease and disability : understanding causes and overcoming injustices - Corrigan, Patrick W. (Washington, DC : American Psychological Association, 2014)
"The lives of people with disease and disability are affected not only by their conditions but by public response to these conditions in the form of stigma and discrimination. Making sense of this injustice is the focus of this book, with chapters on 10 specific illnesses and conditions as well as on the broader issues of courtesy stigma, overcoming stigma, and stigma across cultures. The book concludes with observations on what has not worked in overcoming stigma as well as possible future directions." --Cover.
Part I. Stigma in diseases and disabilities -- ch. 1. Understanding stigma -- ch. 2. Mental illness stigma : types, constructs, and vehicles for change -- ch. 3. The stigma of alcohol and other substance abuse -- ch. 4. Stigma in the field of intellectual disabilities : impact and initiatives for change -- ch. 5. Stigma related to physical and sensory disabilities -- ch. 6. HIV-related stigma -- ch. 7. Infectious diseases : a case study of leprosy-related stigma -- ch. 8. Cancer stigma -- ch. 9. The nature, consequences, and public health implications of obesity stigma -- ch. 10. Stigma associated with disease and disability during childhood and adolescence : a developmental approach -- ch. 11. Stigma and alzheimer's disease : a systematic review of evidence, theory, and methods -- Part II. Stigma and action -- ch. 12. Stigma and family -- ch. 13. Overcoming stigma -- ch. 14. Stigma across cultures -- ch. 15. A critical eye for stigma change.
Includes bibliographical references and index.
Keywords: Chronic diseases -- Psychological aspects; Chronically ill -- Social aspects; People with disabilities -- Public opinion; Sociology of disability